Impairment of optic nerves as the result of cerebral sinus venous thrombosis - Urban, Beata; Bakunowicz-Łazarczyk, Alina (Klinika Oczna / Acta Ophthalmologica Polonica, 2009)
Cerebral venous sinus thrombosis is a disease with potentially serious consequences and usually affecting young to middle aged people. Headache was the most frequent symptom. Diagnosis is based on clinical signs, radiological imaging (CT scan, MRI), bacteriological examinations and laboratory biochemical tests. Mastoidectomy and tympanic cavity drainage is performed in cases with lateral sinus thrombosis in acute mastoiditis. Intravenous antibiotics therapy should be continued for 2 weeks. Anticoagulants should be given, taking into consideration parameters of coagulation system and the type of thrombus. Because of moderate to high mortality rate, patients should be closely monitored. Purpose: Presentation of the case of bilateral optic nerve atrophy after extensive thrombus of sigmoid and right transverse sinuses. Material and methods: We present the case of a boy, who suffered inflammation of venous sinuses of cranial basis, when he was 6 years old. It happened 1 month after right mastoid bone injury. In the course of this disease, intracranial hypertension with bilateral optic disc swelling appeared. Results: 5 years after thrombosinusitis, the child has pale optic discs, changes in the peripheral visual field, abnormal VEP and incorrect contrast sensitivity. Conclusions: Trauma in the region of the temporal bone may cause hard complications from thrombosinusitis, and lead to bilateral optic damage.